Handbook of total quality management - Madu, Christian N. (Christian Ndubisi) (Kluwer Academic, 1998)
This handbook is a reference guide for anyone involved with quality mangement and deployment, including consultants, practitioners and engineers in the professional sector, and students and lecturers on information systems, mangement and industrial egineering.